Strategi Produktivitas Tenaga Kerja dan Daya Saing: Studi Kasus Galangan Kapal Kawasan Pulau Batam dan Jawa - Suwasono, Bagiyo; Widjaja, Sjarief; Zubaydi, Ahmad; Yuliadi, M. Zaed (Universitas Prasetiya Mulya, 2010)
The strength of international competitiveness encouraged a shipyard to reduce cost of materials and labor. Therefore, a shipyard did a measurement to improve the rationalization toward labor productivity. This study aimed to compare the path model from strategies of labor productivity and competitiveness of medium size shipyard in region of Batam and Java. The normality test of questionnaire data at 200 respondents who are competent in the field of shipbuilding through the ratio of skewness and kurtosis did not show normal distribution from the data. Test of model feasibility through PLS algorithm and bootstrapping showed moderate criterion and no significant difference in the variable path for both regions. The first latent variable: shipyard competitiveness is influenced by the strategic policy and labor productivity, while the second latent variable: labor productivity is influenced by work activity, strategic policy, and corporate culture. Test of model segmentation through FIMIX-PLS showed good criterion and no significant difference in the interaction of variable heterogeneity for both regions. The final result of shipyards PLS path modeling showed a consistent relationship between strategic policy and labor productivity in order to increase the Indonesian shipyard competitiveness.